SrxTi0.6Fe0.4O3−δ (x = 1.0, 0.9) catalysts for ammonia synthesis via proton-conducting solid oxide electrolysis cells (PCECs) - Wang, Kaihui; Chen, Huili; Si-Dian, Li; Shao, Zongping (Journal of materials chemistry. A, Materials for energy and sustainability, 2022)
Ammonia is a promising carbon-free energy carrier. Ammonia is usually industrially synthesized via the Haber–Bosch method under high pressures and temperatures, which requires high energy consumption. In comparison, the electrocatalytic reduction of N2 is a green, eco-friendly, and pollution-free method for ammonia synthesis if the electricity is generated using a renewable source. Therefore, the development of highly efficient electrocatalysts for the N2 reduction reaction (NRR) would be significant. Herein, perovskites SrxTi0.6Fe0.4O3−δ (SxTF, x = 1 and 0.9) with tunable oxygen vacancies (OVs) were prepared and used as NRR electrodes for proton-conducting solid oxide electrolysis cells (PCECs). These PCECs were used to synthesize NH3 from N2 and H2. STF and S0.9TF showed maximum ammonia synthesis rates of 6.84 × 10−9 (±0.25 × 10−9) mol cm−2 s−1 and 4.09 × 10−9 (±0.80 × 10−9) mol cm−2 s−1, with corresponding Faraday efficiencies of 2.79% (±0.12%) and 2.01% (±0.09%) at 650 °C and 0.6 V. The enhanced NRR performance of S0.9TF was mainly attributed to the improved adsorption and activation of N2 by the abundant OVs, Ti3+ and the exsolved Fe active particles. This work offers a promising strategy for the design of materials for the electrochemical synthesis of NH3via PCECs.